2019
DOI: 10.1002/jac5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Addressing burnout in clinical pharmacy: What can we learn from other health care disciplines?

Abstract: Burnout is a growing concern across health care disciplines. Burnout is a prolonged response to persistent work-related stressors and includes elements of exhaustion, depersonalization, and perceived ineffectiveness. The body of literature exploring the causes and consequences of burnout has grown substantially. Rates of burnout in clinical pharmacists are similar to those reported for other health care professionals.However, many aspects of burnout have not been adequately characterized in clinical pharmacist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
(91 reference statements)
2
23
0
Order By: Relevance
“…Risk factors associated with the development of burnout are numerous and well‐described (Table ) . Importantly, some of the risk factors for burnout are not necessarily modifiable, while others can potentially be changed.…”
Section: Modifiable and Nonmodifiable Risk Factors For Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors associated with the development of burnout are numerous and well‐described (Table ) . Importantly, some of the risk factors for burnout are not necessarily modifiable, while others can potentially be changed.…”
Section: Modifiable and Nonmodifiable Risk Factors For Burnoutmentioning
confidence: 99%
“…Importantly, the limited literature that is available suggests that burnout is just as prevalent, if not more prevalent, in pharmacy as that of other disciplines . One recent study conducted in the United States found that 53.2% of 329 primarily university health‐system‐based clinical pharmacists demonstrated some aspects of burnout . In another larger study assessing burnout among university‐ and community‐based hospital pharmacists, 61.2% of the 974 survey responders had evidence of burnout .…”
Section: Burnout In Pharmacymentioning
confidence: 99%
“…A Google search yields more than 1.6 million results after typing clinical pharmacist burnout and 11.2 million hits display when the search is expanded to burnout in the medical field. In this edition of JACCP alone, four articles focus on the topic of burnout . Burnout is everywhere!…”
mentioning
confidence: 99%
“…In fact, true burnout syndrome has been around for a long time and there are subgroups of individuals that are at an increased risk of burning out. Between Haase and McQuade and colleagues, both have accurately reviewed available literature and described contributing factors, perceptions, prevalence, and the ultimate impacts of burnout. McQuade and colleagues also acknowledged large heterogeneity in available data .…”
mentioning
confidence: 99%
See 1 more Smart Citation